The Sustained Delivery of Resveratrol or a Defined Grape Powder Inhibits New Blood Vessel Formation in a Mouse Model of Choroidal Neovascularization - Kanavi, Mozhgan Rezaie (Molecules, 2014)
The objective of this study was to determine whether resveratrol or a defined, reconstituted grape powder can attenuate the formation of new blood vessels in a mouse model of choroidal neovascularization (CNV). To accomplish this objective, C57BL/6J mice were randomized into control or treatment groups which received either resveratrol or grape powder by daily oral gavage, resveratrol or grape powder delivered ad libitum through the drinking water, or resveratrol by slow release via implanted osmotic pumps. A laser was used to rupture Bruch’s membrane to induce CNV which was then detected in sclerochoroidal eyecups stained with antibodies against intercellular adhesion molecule-2. CNV area was measured using fluorescence microscopy and Image J software. Ad libitum delivery of both resveratrol and grape powder was shown to significantly reduce the extent of CNV by 68% and 57%, respectively. Parallel experiments conducted in vitro demonstrated that resveratrol activates p53 and inactivates Akt/protein kinase B in choroidal endothelial cells, contributing to its anti-proliferative and anti-migratory properties. In addition resveratrol was shown to inhibit the formation of endothelial cell networks, augmenting its overall anti-angiogenic effects. The non-toxic nature of resveratrol makes it an especially attractive candidate for the prevention and/or treatment of CNV.